Molecular biological diagnostics of adenocarcinomas from an undetected primary focus - Smalyakova, Raisa M. (Journal of the Belarusian State University. Ecology, 2019)
The immunohistochemical characteristics of 160 adenocarcinomas of known localization (breast, prostate, ovarian, lung, pancreas, colon cancer) and 50 adenocarcinoma metastases from an undetected primary focus were analyzed. Nosological forms of metastatic tumors were established on the basis of the morphological assessment of microscopic preparations and the determination of the expression of tissue antigens GCDFP15, ER, TTF1, WT1, CA-125 and CDX2. In 23 patients with metastatic lymphatic lesions from an unexplained primary source, the following metastases were diagnosed: metastasis of lung adenocarcinoma in 18 patients, metastasis of breast cancer - in 3 patients, metastasis of serous ovarian cancer – in 2 patients. In metastatic lesions of supraclavicular lymph nodes in 18 patients the following metastases were diagnosed: metastasis of lung adenocarcinoma in 16 patients, metastasis of breast cancer – in 2. In 9 patients with metastases in axillary lymph nodes from an unknown primary focus the following metastases were diagnosed: metastasis of breast cancer in 7 patients, metastasis lung adenocarcinoma in 2 patients.
Keywords: adenocarcinoma from an undetected primary lesion; metastases; immunohistochemistry; expression; tissue antigens; immunophenotype